Isolation of Vibration Induced in Drive Type Voith Schneider Propeller due to Rotation of Cycloidal Drive - Karim Mohsen, Kadim; Abdalameer Bargash, Reem (International Journal of Engineering and Technology, 2018)
In this paper experimental modal testing was present for propulsion drive type Voith Schneider Propeller, deconvolutionÂ used to decrease the effect of vibration stresses generated by the rotation of cycloidal drive (Voith Schneider Propeller) especially the sing phenomenon also reduce the effect of vibrational critical speeds and to avoiding matching between the frequencies of ship hull and equipment and propeller frequencies with frequency of rotational torque. Reach the reason zone over the maximum velocity by controlling the variables with high accuracy. Experimental testing of Voith Schneider Propeller without structural damping shows a rise in vibration more than in the case of structural damping. When comparing the angles of the blades propeller Â and , it was concluded that when the blades propeller Â is the highest vibration of . The reason for this is because angle Â forces are analyzed into two vertical and horizontal components. Predictive deconvolutionÂ whichÂ is a filtering process which removes a wavelet from the recorded seismic trace by reversing the process of convolution. Suppresses multiple reflections and optionally alters the spectrum of the input data to increase resolution. The commonest way to perform deconvolution is to design aÂ Wiener filterÂ to transform one wavelet into another wavelet in a least-squares sense. By far the most important application is predictive deconvolution in which a repeating signalGood results lead for precise, safe and efficient maneuvering.Â